2002
DOI: 10.1161/01.cir.0000018745.11739.9b
|View full text |Cite
|
Sign up to set email alerts
|

S -Nitroso Human Serum Albumin Treatment Reduces Ischemia/Reperfusion Injury in Skeletal Muscle via Nitric Oxide Release

Abstract: Background-Peroxynitrite generated from nitric oxide (NO) and superoxide (O 2 Ϫ ) contributes to ischemia/reperfusion (I/R) injury. Feedback inhibition of endothelial NO synthase by NO may inhibit O 2 Ϫ production generated also by endothelial NO synthase at diminished local L-arginine concentrations accompanying I/R. Methods and Results-During hindlimb I/R (2.5 hours/2 hours), in vivo NO was monitored continuously (porphyrinic sensor), and high-energy phosphates, reduced and oxidized glutathione (chromatograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
81
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 19 publications
4
81
0
Order By: Relevance
“…However, the involvement of nitric oxide in skeletal muscle ischemia reperfusion injury remains controversial, and has been shown to be both beneficial and deleterious in this setting. It has been reported that administration of an exogenous NO donor can protect against endothelial dysfunction during ischemia reperfusion injury (Hallstrom et al 2002). The exogenous NO exerts a negative feedback on further production of NO by eNOS, and thus limits excessive O 2 formation caused by eNOS derangement in ischemia reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, the involvement of nitric oxide in skeletal muscle ischemia reperfusion injury remains controversial, and has been shown to be both beneficial and deleterious in this setting. It has been reported that administration of an exogenous NO donor can protect against endothelial dysfunction during ischemia reperfusion injury (Hallstrom et al 2002). The exogenous NO exerts a negative feedback on further production of NO by eNOS, and thus limits excessive O 2 formation caused by eNOS derangement in ischemia reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…High-energy phosphates were measured by HPLC as previously described (8,9,22). After incubation of cells with plasma for 90 min, 10 6 cells were centrifuged, washed with 1 ml of PBS, and then deproteinized with 200 l of 0.4 mol/l perchloric acid.…”
Section: Neutrophilsmentioning
confidence: 99%
“…This injury is characterized by initial tissue damage during the ischemic period followed by progressive injury during the reperfusion period. Reperfusion is a trigger for the generation of reactive oxygen species, release of cytokines, induction of adhesion molecules on vascular endothelial cells, and the adhesion and extravasation of leukocytes into postischemic tissue (Hallstrom et al, 2002;Dworschak et al, 2004). Potent cytoprotection against ischemia-reperfusion liver injury in rats (Ikebe et al, 2000) and antibacterial activity in vitro against several types of bacteria (Miyamoto et al, 2000a,b) resulted after human ␣ 1 -protease inhibitor (␣ 1 -PI), an acute phase reactive protein in serum, was S-nitrosylated (SNO-␣ 1 -PI).…”
mentioning
confidence: 99%